2022
DOI: 10.3390/computation10040063
|View full text |Cite
|
Sign up to set email alerts
|

Classifying the Degree of Bark Beetle-Induced Damage on Fir (Abies mariesii) Forests, from UAV-Acquired RGB Images

Abstract: Bark beetle outbreaks are responsible for the loss of large areas of forests and in recent years they appear to be increasing in frequency and magnitude as a result of climate change. The aim of this study is to develop a new standardized methodology for the automatic detection of the degree of damage on single fir trees caused by bark beetle attacks using a simple GIS-based model. The classification approach is based on the degree of tree canopy defoliation observed (white pixels) in the UAV-acquired very hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Remote sensing studies mapping healthy and damaged trees using fine-resolution drone imagery have reported similar high overall accuracies [43,45,70]. Furthermore, similar moderate overall accuracies have been reported when mapping different damage severities, including the classification of the tree-level health status [71,72] and estimation of the damage severity [33,73]. Some confusion occurred between the "minor damage" and "moderate damage" classes.…”
Section: Discussionmentioning
confidence: 60%
“…Remote sensing studies mapping healthy and damaged trees using fine-resolution drone imagery have reported similar high overall accuracies [43,45,70]. Furthermore, similar moderate overall accuracies have been reported when mapping different damage severities, including the classification of the tree-level health status [71,72] and estimation of the damage severity [33,73]. Some confusion occurred between the "minor damage" and "moderate damage" classes.…”
Section: Discussionmentioning
confidence: 60%
“…In addition to conventional time-consuming field surveys, satellite-based images may be a useful tool for detecting defoliations in forest systems. In recent years, there have been several studies using unmanned aerial vehicles (UAV)acquired images, proving to be effective for forestry applications [52,53]. In the case of PPM infestations, this technology may be a useful tool to estimate the infestation severity, even if the number of nests captured by UAV images may be potentially underestimated if some nests on lower branches or in dense stands are not counted.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the higher density of the DPC is important not only for treetop detection, but also for accurate detection of tree canopy characteristics that can be used for the precise evaluation of, for example, forest health [7,9], forest fire disturbance [29], or the estimation of dendrometric parameters [30]. This is especially relevant for fir forests in the Zao Mountains in Japan because, as shown in [22], the rate of single fir tree defoliation can be used as a proxy, and the results of using the TAF will contribute to a higher precision of tree canopy evaluation of the forest stand along the slope.…”
Section: Discussionmentioning
confidence: 99%
“…Fir is a highly valuable tree in Japan because of its obvious ecological function, but mainly as a tourist attraction, as they form the famous "Snow Monsters" in winter when they are covered completely by snow. In recent years, bark beetle attacks have seriously affected fir trees' health [22].…”
Section: Study Sitementioning
confidence: 99%